Towards a Believable Social Robot - Lazzeri, N.; D. Mazzei; A. Zaraki; D. De Rossi (Biomimetic and Biohybrid Systems (Proc. Second International Conference, Living Machines 2013), 2013)
Two perspectives define a human being in his social sphere: appearance and behaviour. The aesthetic aspect is the first significant element that impacts a communication while the behavioural aspect is a crucial factor in evaluating the ongoing interaction. In particular, we have more expectations when interacting with anthropomorphic robots and we tend to define them believable if they respect human social conventions. Therefore researchers are focused both on increasingly anthropomorphizing the embodiment of the robots and on giving the robots a realistic behaviour.This paper describes our research on making a humanoid robot socially interacting with human beings in a believable way.
Keywords: Bioengineering

Towards a smart glove: Arousal recognition based on textile electrodermal response - G. Valenza; A Lanata; E. P. Scilingo; D. De Rossi (Engineering in Medicine and Biology Society (EMBC), 2010 Annual International Conference of the IEEE, 2010)
Keywords: Bioengineering

Towards a Haptic Black Box: Magnetorheological fluid based display for softness and shape discrimination - E. P. Scilingo; N. Sgambelluri; D. De Rossi; A. Bicchi (Proc. IEEE Int. Conf. on Robotics and Automation, 2003)
In this paper we propose an innovative prototype of a haptic display for whole-hand immersive exploration. We envision a new concept of haptic display, the Haptic Black Box concept, which can be imagined as a box where the operator can poke his/her bare hand, and interact with the virtual object by freely moving the hand without mechanical constraints. In this way sensory receptors on the whole operator's hand would be excited, rather than restricting to just one or few fingertips or phalanges. To progress towards such a challenging goal, magnetorheological (MR) fluids represent a very interesting technology. These fluids are composed of micron-sized, magnetizable particles immersed in a synthetic oil. Exposure to an external magnetic field induces in the fluid a change in rheological behaviour turning it into a near-solid in few milliseconds. By removing the magnetic field, the fluid quickly returns to its liquid state. We briefly report on the design of this device, describe psychophysical experiments to assess performance for softness and shape exploration, and report on the experimental results.
Keywords: Haptics

TOWARDS THE REALIZATION OF AN ARTIFICIAL TACTILE SYSTEM - FINE-FORM DISCRIMINATION BY A TENSORIAL TACTILE SENSOR ARRAY AND NEURAL INVERSION ALGORITHMS - A. Caiti; G. Canepa; D. De Rossi; F. Germagnoli; G. Magenes; T. Parisini (IEEE TRANSACTION ON SYSTEMS MAN AND CYBERNETICS, 1995)

Tactile sensing by an electromechanochemical skin analog - D. De Rossi; L. Lazzeri; C. Domenici; A. Nannini; P. Basser (SENSORS AND ACTUATORS, 1989)
Keywords: Bioengineering

Tactile sensors and the gripping challenge - P. Dario; D. De Rossi (IEEE SPECTRUM, 1985)
Keywords: Bioengineering

Techniques and transducers for non-invasive measurement of physiological parameters - D. De Rossi (ELETTROMEDICALI, 1982)
Keywords: Bioengineering

Touch-sensitive polymer skin uses piezoelectric properties to recognize orientation of objects - P. Dario; R. Bardelli; D. De Rossi; L.R Wang; P. C. Pinotti (SENSOR REVIEW, 1982)
Keywords: Bioengineering

Trasduttori acustici a polimeri piezoelettrici - D. De Rossi; R. Bardelli; P. Dario; C. Domenici; F. Pedrini (RIVISTA ITALIANA DI ACUSTICA, 1982)
Keywords: Bioengineering